2006
DOI: 10.1577/h05-025.1
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Replication of Edwardsiella ictaluri in Channel Catfish Macrophages

Abstract: The ability of Edwardsiella ictaluri to enter, survive, and replicate in head kidneyÀderived macrophages from channel catfish Ictalurus punctatus was investigated in vitro. Primary macrophage cultures were exposed to E. ictaluri and were sampled after 0 (90 min postinfection), 4, 8, and 12 h. The data indicated that bacterial numbers for E. ictaluri increased 2.6-, 5.1-, and 7.1-fold after 4, 8, and 12 h of incubation, respectively. Microscopic examination of infected cell cultures revealed numerous intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 30 publications
1
63
0
Order By: Relevance
“…The ability to survive intracellularly is crucial for several bacterial fish pathogens after invasion of their eukaryotic target cells (16,22,41). Distinct subpopulations of macrophages derived from goldfish (Carassius auratus) kidney leukocyte cultures were previously characterized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ability to survive intracellularly is crucial for several bacterial fish pathogens after invasion of their eukaryotic target cells (16,22,41). Distinct subpopulations of macrophages derived from goldfish (Carassius auratus) kidney leukocyte cultures were previously characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Effective internalization by both cell types was partially mediated by a heat-sensitive serum component, presumably complement. Complement and/or complement receptors (CR) have been associated with efficient internalization of many mammalian and fish pathogens, including F. tularensis, Mycobacterium spp., Listeria monocytogenes, and Edwardsiella ictaluri (6,12,13,16,22). With the F. tularensis live vaccine strain (LVS), optimal phagocytosis by dendritic cells (DC) is dependent on complement factor C3-derived opsonins and the major complement receptors expressed by DC, the integrins CR3 (CD11b/CD18) and CR4 (CD11c/CD18) (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the pathogenesis of E. ictaluri was reviewed in 1993 (28,31), recent reports demonstrated that E. ictaluri is a facultative intracellular pathogen (3) and that a type III secretion system is required for intracellular survival and replication within channel catfish head kidney-derived macrophages (HKDM) (30). Using signature-tagged mutagenesis (STM) in an immersion challenge model for E. ictaluri, Thune et al (30) identified 50 transconjugants carrying transposon insertions in genes required for survival and replication in the channel catfish host.…”
mentioning
confidence: 99%